Explaining fear of crime among university students: A comparison between national and international students in Istanbul - Özaşçılar, Mine (International review of victimology, 2024)
Past studies have highlighted the importance of studying the fear of crime among international students. Interestingly, though, most of this research has been in developed societies and has not directly compared international and indigenous/national students. To fill this gap, the current study aims to examine the determinants of fear of crime among domestic and international students in Turkey. Drawing upon a survey of 377 international students and 579 national university students studying in Istanbul, Turkey, during the Fall 2019 semester, the study finds that international students mostly feared being cheated or ‘conned’. In contrast, for the domestic students the threat from physical attack was of most concern. The results also indicate that among all gender groups for international and domestic students, female international students reported higher levels of fear of crime than all other sub-groups.